2004
DOI: 10.1099/mic.0.27217-0
|View full text |Cite
|
Sign up to set email alerts
|

A linear megaplasmid, p1CP, carrying the genes for chlorocatechol catabolism of Rhodococcus opacus 1CP

Abstract: The Gram-positive actinobacterium Rhodococcus opacus 1CP is able to utilize several (chloro)aromatic compounds as sole carbon sources, and gene clusters for various catabolic enzymes and pathways have previously been identified. Pulsed-field gel electrophoresis indicates the occurrence of a 740 kb megaplasmid, designated p1CP. Linear topology and the presence of covalently bound proteins were shown by the unchanged electrophoretic mobility after S1 nuclease treatment and by the immobility of the native plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 49 publications
0
15
0
1
Order By: Relevance
“…Most remarkably, it had been shown that certain enzymes must have evolved divergently to those ones typical for proteobacteria providing functional convergence (Eulberg et al ., ; Moiseeva et al ., ). Genes for the 3‐chlorocatechol‐catabolic pathway have been identified to be located on a 740‐kb large linear megaplasmid p1CP (König et al ., ). With the exception of a benzoate‐catabolic gene cluster (Bauer, ), little is known on enzyme activities of peripheral degradation, their genetic localization and on their degree of redundancy in strain 1CP.…”
Section: Introductionmentioning
confidence: 97%
“…Most remarkably, it had been shown that certain enzymes must have evolved divergently to those ones typical for proteobacteria providing functional convergence (Eulberg et al ., ; Moiseeva et al ., ). Genes for the 3‐chlorocatechol‐catabolic pathway have been identified to be located on a 740‐kb large linear megaplasmid p1CP (König et al ., ). With the exception of a benzoate‐catabolic gene cluster (Bauer, ), little is known on enzyme activities of peripheral degradation, their genetic localization and on their degree of redundancy in strain 1CP.…”
Section: Introductionmentioning
confidence: 97%
“…Digoxigenin (DIG) labeling, blotting, hybridization, and detection procedures were performed as described previously (29). A 688-bp BamHI/SpeI fragment of plasmid p1CPS1 served as a template for probe preparation, and genomic 1CP DNA was digested with the endonucleases ApaI, BamHI, EcoRI, and PstI.…”
mentioning
confidence: 99%
“…For detection of extra chromosomal DNA, plasmid isolation and pulse field gel electrophoresis assays were developed as described by König and colleagues (). Yeast Chromosome PFG marker (New England Biolabs, IZASA, Barcelona, Spain) was used as reference.…”
Section: Methodsmentioning
confidence: 99%